Neonatal vaginal irritation results in long-term visceral and somatic hypersensitivity and increased hypothalamic–pituitary–adrenal axis output in female mice. Issue 10 (October 2015) - Pierce, Angela N.; Zhang, Zhen; Fuentes, Isabella M.; Wang, Ruipeng; Ryals, Janelle M.; Christianson, Julie A.
Abstract : Abstract: Experiencing early life stress or injury increases a woman's likelihood of developing vulvodynia and concomitant dysregulation of the hypothalamic–pituitary–adrenal (HPA) axis. To investigate the outcome of neonatal vaginal irritation (NVI), female mouse pups were administered intravaginal zymosan on postnatal days 8 and 10 and were assessed as adults for vaginal hypersensitivity by measuring the visceromotor response to vaginal balloon distension (VBD). Western blotting and calcium imaging were performed to measure transient receptor potential ankyrin 1 (TRPA1) and vanilloid 1 (TRPV1) in the vagina and innervating primary sensory neurons. Serum corticosterone (CORT), mast cell degranulation, and corticotropin-releasing factor receptor 1 (CRF1 ) expression were measured as indicators of peripheral HPA axis activation. Colorectal and hind paw sensitivity were measured to determine cross-sensitization resulting from NVI. Adult NVI mice had significantly larger visceromotor response during VBD than naive mice. TRPA1 protein expression was significantly elevated in the vagina, and calcium transients evoked by mustard oil (TRPA1 ligand) or capsaicin (TRPV1 ligand) were significantly decreased in dorsal root ganglion from NVI mice, despite displaying increased depolarization-evoked calcium transients. Serum CORT, vaginal mast cell degranulation, and CRF1 protein expression were all significantly increased in NVI mice, as were colorectal and hind paw mechanical and thermal sensitivity. Neonatal treatment with a CRF1 antagonist, NBI 35965, immediately before zymosan administration largely attenuated many of the effects of NVI. These results suggest that NVI produces chronic hypersensitivity of the vagina, as well as of adjacent visceral and distant somatic structures, driven in part by increased HPA axis activation. Abstract : Neonatal irritation of the vagina permanently sensitizes the vagina and distant somatic structures in a corticotrophin-releasing factor-dependent manner.